Physicians' Attitudes toward Adolescent Confidentiality Services: Scale Development and Validation - Jeremić Stojković Vida; Cvjetković Smiljana; Matejić Bojana (Sciendo, 2020)
Confidentiality is one of the oldest ethical principles in healthcare. However, confidentiality in adolescent healthcare is not a universally-accepted doctrine among scholars. The ethical acceptability of confidential services in adolescents' healthcare is based on perceptions of adolescent maturity and an appreciation of its importance to adolescents' access and utilization of healthcare services. Despite legal policies that promote adolescents' rights, physicians' attitudes toward adolescent confidentiality can be a determining factor in their ultimate decision to protect adolescents' confidentiality.